The Contents of Some Trace Elements (As, Br, Cu, Hg, Se, and Zn) in Mytilus galloprovincialis Mussels From Agigea Port, Romania - Bucşe, Andra; Pârvulescu, Oana Cristina; Vasiliu, Dan; Mureșan, Mihaela (Frontiers in Marine Science, 2022)
This study aimed at assessing the accumulation of some trace elements (arsenic, bromine, copper, mercury, selenium, and zinc) in the soft tissue of Mediterranean mussels (Mytilus galloprovincialis) from the Black Sea, near Agigea Port. The mussel samples were collected on a monthly basis between February and June 2019 from two stations located in front of the Danube–Black Sea Canal lock, along the two artificial dikes. The mussels (260 samples) were divided into three classes according to their length: A (3−5.9 cm), B (6−8.9 cm), and C (9−12 cm). The concentrations (dry basis) of As (12.5 ± 3.0 mg/kg), Br (173.6 ± 53.9 mg/kg), Cu (11.2 ± 2.5 mg/kg), Hg (0.02 ± 0.02 mg/kg), Se (2.9 ± 1.1 mg/kg), and Zn (179.5 ± 2.5 mg/kg) were determined using spectrometric techniques. The mean daily values of the physicochemical parameters of seawater (temperature, salinity, pH, chlorophyll a content, and dissolved oxygen content) within the study area were reported. Higher element concentrations were generally found for mussels from size classes A and B compared with those of the larger and older mussels from class C. Principal component analysis (PCA) suggested that the phytoplankton represented an important source of As and Br for the smaller mussels collected in February (when the levels of seawater temperature were lower and those of pH and salinity higher) compared to the larger mussels collected in June. Moreover, the multivariate analysis suggested that Cu, Se, Zn, and Br originated from similar anthropogenic sources and their higher concentrations reported in February and June were obtained at lower levels of seawater salinity. The contents of Cu, Zn, Se, As, and Hg in the mussel soft tissue were lower than the maximum permissible levels.